Why have some Indian states performed better than others at reducing rural poverty? - Datt, Gaurav; Ravallion, Martin (International Food Policy Research Institute, 1997)
Rural poverty rankings of Indian states in 1990 were very different from 1960. This unevenness in progress allows us to study the causes of poverty in a developing rural economy. We model the evolution of various poverty measures, using pooled state-level data for the period 1957-91. Differences in trend rates of poverty reduction are attributed to differing growth rates of farm yield per acre, and differing initial conditions; states starting with better infrastructure and human resources saw significantly higher long-term rates of poverty reduction. Deviations from the trend are attributed to inflation (which hurt the poor in the short term) and shocks to farm and nonfarm output.